Works councils, collective bargaining, and apprenticeship training - evidence from German firms - Kriechel, Ben [Verfasser]; Mühlemann, Samuel [Verfasser]; Pfeifer, Harald [Verfasser]; Schütte, Miriam [Verfasser] (My University, 2014)
"In this paper, we investigate the effects of works councils on apprenticeship training in Germany. The German law attributes works councils substantial information and co-determination rights to training-related issues. Thus, works councils may also have an impact on the cost-benefit relation of workplace training. Using detailed firm-level data containing information on the costs and benefits of apprenticeship training, we find that firms with works councils make a significantly higher net investment in training compared to firms without such an institution. We also find that the fraction of former trainees still employed with the same firm 5 years after training is significantly higher in the presence of works councils, thus enabling firms to recoup training investments over a longer time horizon. Furthermore, all works council effects are much more pronounced for firms covered by collective bargaining agreements." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 3.5.4 Sozialpartner; S 4.2 Kostenarten; S 4.1 Finanzierungsquellen; Betriebliche Berufsausbildung; Betriebsrat; Auswirkung; Ausbildungsbetrieb; Ausbildungskosten; Ausbildungsinvestition; Kosten-Nutzen-Analyse; Mitbestimmung; Betriebsgröße; Betriebstreue; Tarifverhandlungen